Activity of acetylcholinesterase (AChE) in male albino rats exposed to metal welding fumes in an experimental setting - Ali Sani; Ibrahim Lawal Abdullahi; Sani Ibrahim (Environmental Health Engineering and Management, 2021)
Background: There are millions of workers in the world, who engage in activities associated with welding operations but are not classified as full-time metal workers. The present study aimed to determine the activity of acetylcholinesterase (AChE) in blood of laboratory animals exposed to welding fumes. Methods: Welding fumes were obtained from Kofar Ruwa, Kano by a skilled welder. 130 albino rats were purchased from the Animal Section of Department of Biological Sciences and were divided into 12 groups. They were given doses equivalent to the workers’ real life exposure regimes, and 1 group was selected as control group. They were administered intratracheally following anesthetization once weekly for twelve weeks. The rats were euthanized and serum samples were collected. Then, AChE activity was evaluated spectrophotometrically using ELISA kit (Sunlong Biotech Company). Results: The mean values of AChE ranged from 23.1 to 25.05 ng/mL with the control having a value of 24.7 ng/mL. Thus, there was a decrease in the values of AChE in the blood of treated groups, which was significantly different from the control (P < 0.05). Conclusion: Metal welding fumes negatively affected the AChE by reducing its mean values. This implies that welding fumes possesses neurotoxic effects, which can lead to some neurodegenerative diseases.